An assessment of traffic congestion in Taman Sri Serdang, Selangor, Malaysia - Fahmi, Afiq Haikal; Sahrir, Syazwani; Nik Ab Rahim, Nik Nor Rahimah (Malaysian Institute of Planners, 2023)
The issue of traffic congestion has emerged as a significant and multifaceted challenge in numerous cities worldwide, encompassing substantial economic and environmental implications. Numerous experts have proposed that the foremost measure to address the congestion issue is to identify the characteristics of traffic congestion. This study aimed to assess the traffic congestion in urban road networks. Thus, the main methodological approach for conducting the study was the traffic volume study in Taman Sri Serdang, which was observed to examine the traffic flow during weekdays and weekends to examine the traffic flow patterns. Accordingly, conducting a traffic volume and Level of Service (LOS) analysis is necessary to enhance accessibility and road capacity. A comparison of the traffic trends and LOS during weekdays and weekends was also discussed. The findings concerning peak-hour traffic patterns are highlighted, and the conclusions are derived regarding urban traffic flow patterns.